Multiple intracranial dural arterivenous fistulas in a girl with Cowden Syndrome – a case report - Singh, Vineeta; Neil, Terry; Hetts, Steven W.; English, Joey D. (Journal of Pediatric Neuroradiology, 2014)
Dural arteriovenous fistulas (DAVFs) are abnormal arteriovenous shunts that occur in the dura of the central nervous system. Multiple DAVFs present in a nine year old girl with Cowden Syndrome (CS) diagnosis is presented in this article.
Keywords: DAVF; Cowden Syndrome; Vascular malformations